Examining U.S. foreign policy after the cold war- multilateralism. - Lim, Wee Kwong. (2008)
With the end of the Cold War, U.S. foreign policy has evolved from containment to multilateralism. However, U.S. met with several failures in employing multilateralism in Somalia, Haiti and Bosnia. This led to the debate of multilateralism being an effective foreign policy in the post Cold War era.